possible association of HLA class-1 molecules with colorectal cancer in Iraqi patients - AL-Ghurabi, batool H.; AL-Hassan, ahmed A.; AL-Naseri, sana’a A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: